The effect of students’ knowledge at the accounting department upon the interest of working as an accountant in a company - Rizki Ahmad Fauzi (STIE Binaniaga, 2020)
Choice in career is a process in choosing a job for his life. One career field that has a high chance is to be an accountant in a company. There are several things that can influence a person's decision in choosing a career. This study aims to determine the effect of knowledge of accounting department students on work interest in becoming an accountant in a company. This type of research is quantitative research with the expost facto method. Data was collected by distributing questionnaires to respondents. The population of this study was accounting students at the Diploma program at STIE Binaniaga. The method used to determine the sample is the purposive sampling method. Data analysis was carried out using a simple linear regression method. The results of this study indicate that there is an influence of knowledge on the interest in becoming an accountant in the company. Keywords: Accountant, Interest, Knowledge